Customers satisfaction towards service quality among “Mamak” restaurants at Bandar Hilir, Malacca / Hazwani Ismail, Nur Hisyam Kamaruddin and Raja Anis Aniza Raja Mohd Yusof - Ismail, Hazwani; Kamaruddin, Nur Hisyam; Raja Mohd Yusof, Raja Anis Aniza (2014)
The study seeks to determine the service quality of the “Mamak” restaurants that will influence satisfaction of customers in hospitality industry. In Malaysia, the term “Mamak” refers to Tamil Muslims who generally the owners and also the operators of such restaurants. Basically, the findings showed that the food quality, price, physical environment, restaurant service management, restaurant brand personality and employees job satisfaction related to each other in order to fulfill the customer’s satisfaction towards the restaurant. The study for this topic will give benefits to owner restaurant to improve their service quality in their restaurants in order to return customer loyalty. The research found that service quality significantly affects customer satisfaction which has strong impact on customer loyalty. According to Robust and statistically significant, restaurant that pay attention to food quality, appropriate cost, and attentive service have the greatest chance to increase guests’ intention to return. The questionnaire and survey are used in this study to determine the customer satisfaction towards service quality at “Mamak” restaurants. Besides, case studies use a large list of consumer kept by a major online marketing research company.